Locus de controle e características de personalidade em indivíduos portadores de úlcera e hipertensão: um estudo exploratório - Palharini, Francisco de Assis (1985)
The present study presupposes that the concepts of 'tension', 'stress', and 'anxiety factors' are neither sufficient nor adequate, in the present stage of the research in psychology, to explain the occurence ·of the so called psychosomatic disturbs in terms of antecedent variable. The concept of locus of control as it has been formulated by Rotter is used and investigated in this study through th Scale Internal-External, as we interpret experimental situations in a series of studies reported as having a common denominator: the difficulty in perceiving the control as having .been originated in the subject's action. We also investigate the incidence of organic disturbe, possible differences in personality factors, and the association with birth order. The data collected indicate that subjects who suffer from ulcers and/or hypertension tend to respond externally in the Scale 'I-E, which provides a basis for our interpretations of the studies reported. There is also evidence that the birth order (eldest and other (s)) is associated with the presence of these disturbs. Besides this, these is, according to our instrument, a higher occurrence of organic disturbs in such subjects. Finally, ne have observed that, among the personality factors investigated, only one distinguishes subjects who have ulcers and/or hypertension from the healthy ones: the tendency to neuroticism, which is ' predominant in the experimental group.